Application of Fuzzy Delphi Method in developing a construct of the Malaysian Armed Forces spiritual assessment - Abdul Aziz, Azlisham; Mamat, Mohd Nor; Mohamed Salleh, Daud; Said, Norazura; Ismail, Zulkifli; Ahmad Hasanuddin, Pg; Samichan, Aziah; Abdul-Hamid, Fazli (INT-JESCE Publications, 2022)
In line with the Strategic Management System Plan of the Malaysian Armed Forces 2021 – 2025, the spiritual aspect in the core values to develop defence human resources are emphasized. Therefore, this research was implemented to develop the construct of the dimension of appreciation of faith in assessing the spirituality of human defence by the panel of experts' agreement in developing the construct of the dimension of the evaluation. The researcher used the Design and Development Research (DDR) approach in producing this study. In the context of this article, the researcher discusses the consensus phase process of a panel of 15 experts on the construct of faith appreciation. The process aims to obtain consensus agreement on the construct of assessment of faith appreciation and determine the position of the items. This process applies the Fuzzy Delphi Method (FDM) based on a 7-point linguistic scale questionnaire. The collected data were subsequently analyzed using fuzzy triangle numbering. The position of each construct was determined using a defuzzification process. The research findings concluded that the expert panel agreed to all items for constructs under the faith appreciation dimension of spiritual evaluation with defuzzification value exceeding a – cut value = 0.5 (threshold value was ≤ 0.2 and expert agreement exceeded 75%). Next, the application process of the Fuzzy Delphi method shows that the constructs of belief in Allah, belief in angels, belief in the Quran, belief in the messenger, belief in the hereafter and belief in qada and qadar (fate and destiny) have reached a good agreement. The application process of the FDM has resulted in a consensus construct of the dimension of appreciation of the creed of spiritual evaluation. Therefore, it can contribute to developing the dimension of spiritual evaluation of the Malaysian military